Rancang Bangun Perangkat Mobile Berbasis Delay Tolerant Network Sebagai Perantara Pengiriman Data Sensor Dari Lapangan Ke Pusat Data - Hendra Danu Laksana; Adhitya Bhawiyuga; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Internet of Things (IoT) consist of three main components: hardware, middleware, and presentation. The emerging problem is used hardware in sensor node have constrained processor and memory ability. Therefore, sensor node only functionate as sensor data reader and sender to data center for data analysis and decision making. Data sending in IoT system from sensor node to data center can use several protocol, but no one of those procotols can be used in intermittent connected network. Attempting to overcome these problems, a system that implements the mechanism of store-carry-forward data transmission is designed in this research. One of communication mechanism that implement store-carry-forward is Delay Tolerant Network. The designed mechanism will be applied to Android OS-based mobile device. The test results state that the system can transmit messages with a 100% success rate even when inter-device connection conditions are intermittently connected and the average delay is 51.8 seconds. The test result also states that the system is not too burdensome device because the device specifications that exist today is very qualified to accommodate the load.